2009
DOI: 10.1007/s12539-009-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modeling of the NS 3 helicase of Tick-borne encephalitis virus and their virtual screening of potent drugs using molecular docking

Abstract: Homology modeling of NS3 helicase in Tick-borne encephalitis virus using known protein crystal structure was done. Its 3-D structure was evaluated and validated using PROCHECK comprising amino acid residues in favored region of Ramachandran plot. Helicase forms a large family of proteins which ubiquitously distributes in wide variety of organisms. It plays crucial role in transcription and replication of single-stranded viral RNA genomes. Consequently, NS3 represents an interesting target for the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…These results demonstrated that ribavirin could strongly inhibit TBEV propagation in the susceptible cells at a non-cytotoxic dose range. In agreement with our results, on the basis of protein-drug interactions, ribavirin potently inhibited TBEV by targeting TBEV NS3 helicase ( Singh and Somvanshi, 2009 ). Ribavirin significantly inhibited the proliferation of the highly virulent strain of the TBEV in the PK cell cultures ( Krylova and Leonova, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…These results demonstrated that ribavirin could strongly inhibit TBEV propagation in the susceptible cells at a non-cytotoxic dose range. In agreement with our results, on the basis of protein-drug interactions, ribavirin potently inhibited TBEV by targeting TBEV NS3 helicase ( Singh and Somvanshi, 2009 ). Ribavirin significantly inhibited the proliferation of the highly virulent strain of the TBEV in the PK cell cultures ( Krylova and Leonova, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…The 3-D structure of 3-oxoacyl-acyl carrier protein synthase II contributed in the synthesis of fatty acid which is essential for cell growth and viability of M. tuberculosis using homology modeling [27]. The homology modeling of NS3 helicase in Tick-borne encephalitis virus using known protein crystal structure has been reported for the development of specific anti-TBEV therapies [28]. The two-component bacterial systems involve sensor histidine kinase (SHK) and its response regulators are considered as a lucrative target for drug design.…”
Section: Introductionmentioning
confidence: 99%